Elevated Nicotinamide Phosphoribosyl Transferase in Skeletal Muscle Augments Exercise Performance and Mitochondrial Respiratory Capacity Following Exercise Training - Brouwers, Bram; Stephens, Natalie A.; Costford, Sheila R.; Hopf, Meghan E.; Ayala, Julio E.; Yi, Fanchao; Xie, Hui; Li, Jian-Liang; Gardell, Stephen J.; Sparks, Lauren M.; Smith, Steven R. (Frontiers in Physiology, 2018)
Mice overexpressing NAMPT in skeletal muscle (NamptTg mice) develop higher exercise endurance and maximal aerobic capacity (VO2max) following voluntary exercise training compared to wild-type (WT) mice. Here, we aimed to investigate the mechanisms underlying by determining skeletal muscle mitochondrial respiratory capacity in NamptTg and WT mice. Body weight and body composition, tissue weight (gastrocnemius, quadriceps, soleus, heart, liver and epidydimal white adipose tissue), skeletal muscle and liver glycogen content, VO2max, skeletal muscle mitochondrial respiratory capacity (measured by high-resolution respirometry), skeletal muscle gene expression (measured by microarray and qPCR) and skeletal muscle protein content (measured by western blot) were determined following six weeks of voluntary exercise training (access to running wheel) in 13-week-old male NamptTg (exercised NamptTg) mice and WT (exercised WT) mice. Daily running distance and running time during the voluntary exercise training protocol were recorded. Daily running distance (p=0.51) and running time (p=0.85) were not significantly different between exercised NamptTg mice and exercised WT mice. VO2max was higher in exercised NamptTg mice compared to exercised WT mice (p=0.02). Body weight (p=0.92), fat mass (p=0.49), lean mass (p=0.91), tissue weight (all p>0.05), and skeletal muscle (p=0.72) and liver (p=0.94) glycogen content were not significantly different between exercised NamptTg mice and exercised WT mice. Complex I oxidative phosphorylation (OXPHOS) respiratory capacity supported by fatty acid substrates (p<0.01), maximal (complex I+II) OXPHOS respiratory capacity supported by glycolytic (p=0.02) and fatty acid (p<0.01) substrates, and maximal uncoupled respiratory capacity supported by fatty acid substrates (p<0.01) was higher in exercised NamptTg mice compared to exercised WT mice. Transcriptomic analyses revealed differential expression for genes involved in oxidative metabolism in exercised NamptTg mice compared to exercised WT mice, specifically, enrichment for the gene set related to the SIRT3-mediated signaling pathway. SIRT3 protein content correlated with NAMPT protein content (r=0.61, p=0.04). In conclusion, NamptTg mice develop higher exercise capacity following voluntary exercise training compared to WT mice, which is paralleled by higher mitochondrial respiratory capacity in skeletal muscle. The changes in SIRT3 targets suggest that these effects are due to remodeling of mitochondrial function.